Relevansi Konsep Rahmatan Lil ‘Alamin Terhadap Toleransi Beragama - Hadi, Nur; Wasehudin; Najla Surbakti, Naila; Elia Martatiningsih Arum, Ai; Nuraffiatul Jannah, Diah (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
The concept of Rahmatan lil'alamin has strong relevance to religious tolerance, and how an understanding of inclusivity can play a central role in building a society that respects and accepts differences in religious beliefs. This research or study explains that there is a relevance or relationship of rahmatanLil'Alamin against religious tolerance. The goal is to make it understandable for some people to apply concept of Islamic teachings Rahmatan Lil'Alamin in their lives so that peace, happiness, serenity and harmony can be realized. The research method used is the library method, namely reading various books, collecting and recording book literature with data sources found in the library. The results of the discussion in this journal are that in the context of religious tolerance, the conceptt of rahmatan lil alamin can to interpreted as an inclusive attitude that encourages Muslims to respect, accept and establish harmonious relationships with people of other religions, teaches Muslims about the importance of love, compassion, and kindness to all human beings and the environment.